INTEGRATED-HOLISTIC TEACHING PROTOTYPE FOR ENGLISH LESSON AT ISLAMIC SCHOOL: STEP FOR BUILDING HOLISTIC STUDENTS - Rohmah, Galuh Nur; Fitriyah, Ulil; Hanifiyah, Lina (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2023)
English teachers often face confusion to relate between the materials and religious values especially teachers of Islamic school who should strongly show the relation. This paper aims to develop a teaching prototype as a guideline leading to the integration of religious values into English lesson for Islamic Junior High School.  Design-based research was used as research method in which need analysis was initially done for gaining EFL teachers’ reflection and aspiration on their English class, and their understanding on integration of Islamic values. Three English teachers from both pesantren-based and non pesantren-based were involved as the research subjects. The need analysis was the basis for the prototype which then followed by expert judgment to shape the quality of prototype and future direction for integrated-holistic teaching. The study showed that integrated-holistic teaching for English lessons could cover spiritual, emotional, intellectual, and social dimensions which are very essential for students to be holistic/insan kamil students. In conclusion, English teachers are strongly possible to contextualize  the prototype. Pedagogical implication of the study could be manifested by the existing clear direction for teaching English holistically. This study is not free from limitation. It needs to be more operationalized to potentially build students who are spiritually, intellectually, emotionally, and socially mature.